Mobility, temporality, and social reproduction: everyday rhythms of the 'FIFO family' in the Australian Mining Sector. Issue 1 (2nd January 2020) - Mayes, Robyn
Abstract: The substantial use of Fly-in-Fly out (FIFO) work in the Australian mining sector involves a repeated cycle in which workers (mostly men) leave their homes to undertake a pre-determined number of consecutive days of work on (often remote) mine sites where they are also accommodated. They then spend a pre-determined number of days at home. This article examines how FIFO workers' rhythms of physical absence and presence in family life shape the everyday mobilities and temporalities of their emplaced spouses as they undertake the work of social reproduction. It thus brings a gendered lens to the emergent literature examining interconnections of mobility and temporality. Drawing on in-depth interviews with twenty female partners of male FIFO mine workers, the analysis identifies the entangled ways in which this labour mobility profoundly reshapes women's mobilities and interrelated experiences and organisation of social time. In particular, 'the weekend' emerges as a time of profound disjuncture for FIFO spouses who feel 'out of kilter' with conventional social rhythms associated with 9-5 work. The article thus elucidates contemporary intersections of changing formations of capitalism and the rhythms of social reproduction.